Various response functions in lattice domes reliability via analytical integration and finite element method - Pakusiński, Bartłomiej; Kamiński, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The main aim of this work is to verify an influence of the response function type in direct symbolic derivation of the probabilistic moments and coefficients of the structural state variables of axisymmetric spherical steel dome structures. The second purpose is to compare four various types of domes (ribbed, Schwedler, geodesic as well as diamatic) in the context of time-independent reliability assessment in the presence of an uncertainty in the structural steel Young modulus.
Keywords: response function method; semi-analytical probabilistic technique; lattice dome structures; reliability analysis; weighted least squares method